The effect of saddle design on stresses in the perineum during cycling - Spears, I. R.; Cummins, N. K.; Brenchley, Z.; Donohue, C.; Turnbull, C.; Burton, S.; Macho, G. A. (Medicine & Science in Sports & Exercise, 2003)
PURPOSE: Repetitive internal stress in the perineum has been associated with soft-tissue trauma in bicyclists. Using an engineering approach, the purpose of this study was to quantify the amount of compression exerted in the perineum for a range of saddle widths and orientations. METHODS: Computer tomography was used to create a three-dimensional voxel-based finite element model of the right side of the male perineum-pelvis. For the creation of the saddle model, a commercially available saddle was digitized and the surface manipulated to represent a variety of saddle widths and orientations. The two models were merged, and a static downward load of 189 N was applied to the model at the region representing the sacroiliac joint. For validation purposes, external stresses along the perineum-saddle interface were compared with the results of pressure sensitive film. Good agreement was found for these external stresses. The saddles were then stretched and rotated, and the magnitude and location of maximum stresses within the perineum were both recorded. In all cases, the model of the pelvis-perineum was held in an upright position. RESULTS: Stresses within the perineum were reduced when the saddle was sufficiently wide to support both ischial tuberosities. This supporting mechanism was best achieved when the saddle was at least two times wider than the bi-ischial width of the cyclist. Stresses in the anterior of the perineum were reduced when the saddle was tilted downward, whereas stresses in the posterior were reduced when the saddle was tilted upward. CONCLUSIONS: Recommendations that saddles should be sufficiently wide to support the ischial tuberosities appear to be well founded. Recommendations that saddles be tilted downward (i.e., nose down) are supported by the model, but with caution, given the limitations of the model.